The Influence of Selected Meteorological Factors on Microbial Biomass and Mineralization of Two Organic Fertilizers - Mignon S. SANDOR; Traian BRAD; Aurel MAXIM; Constantin TOADER (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2011)
A mesocosm study was conducted in order to evaluate the effects of short-term rainfall and temperature variation on soil microbial biomass and bacteria to fungi ratio. In addition, the relation between the decomposition process of two organic fertilizers, cattle manure and barley straw, and the activity of soil microbial biomass was also studied. In order to assess the effect of biological activity on soil fertility the dynamics of soil pH, N-NO3-, N-NH4+, Corg and Nt during plant growing season was measured. The results suggest that short-term variation of climate had a significant effect on microbial biomass with dry periods distinguished by a reduced microbial biomass compared to wet periods. The ratio bacteria to fungi seems also to be sensitive to variations in rainfall and temperature regime, however further studies are required to draw a definitive conclusion. Regarding the type of fertilizer used, the straw treatments showed higher microbial biomass than the manure treatments, but higher decomposition rate was observed in manure fertilized soil. The effect of soil biological activity on soil pH was limited for both manure and straw treatments while the changes of the soil nitrate amounts are related to the microbial biomass. The study indicates that nitrate immobilization and mineralization processes are influenced by meteorological conditions and microbial biomass dynamics. In contrast, soil organic carbon and total nitrogen did not seem to be affected by variations in temperature, rainfall and microbial activity.